HBC-porphyrin-close contact chromophores - Englert, Jan; Malig, Jenny; Zamolo, Valeria Anna; Hirsch, Andreas; Jux, Norbert (Chemical Communications, 2013)
A photo/redoxactive hexa-peri-hexabenzocoronene-porphyrin conjugate with a direct connection between the two chromophores was synthesised using a formylated hexaphenylbenzene precursor. © 2013 The Royal Society of Chemistry.